Development of a System for Static Analysis of C ++ Language Code - Adamenko, Yu.V.; Medvedev, A.A.; Karpunin, D.A. (2020 International Multi-Conference on Industrial Engineering and Modern Technologies (FarEastCon), 2020)
The main goal of the system is to make it easier to standardize the style of program code written in C++. Based on the results of the review of existing static analyzers, in addition to the main requirements, requirements for the structure of stylistic rules were identified. Based on the results obtained, a system for static analysis of the C++ language has been developed, consisting of a set of modules. The system is implemented using the Python 3.7 programming language. HTML and CSS markup languages were used to generate html reports. To ensure that rules can be stored in the database, the MongoDB database management system and the pymongo driver module were used.